Species diversity and molecular characterization of Alternaria section Alternaria isolates collected mainly from cereal crops in Canada - Dettman, Jeremy R.; Eggertson, Quinn A.; Kim, Natalie E. (Frontiers in Microbiology, 2023)
Alternaria is often one on the most abundant fungal genera recovered from a wide array of plant hosts and environmental substrates. Many species within the sub-generic Alternaria section Alternaria are common plant pathogens that cause pre-harvest losses due to reduced productivity and post-harvest losses due to spoilage and contamination with mycotoxins. As certain species of Alternaria may have distinct mycotoxin profiles, and very broad host ranges, understanding the distribution of species by geography and host is critical for disease prediction, toxicological risk assessment, and guiding regulatory decisions. In two previous reports, we performed phylogenomic analyses to identify highly informative molecular markers for Alternaria section Alternaria, and validated their diagnostic ability. Here, we perform molecular characterization of 558 section Alternaria strains, collected from 64 host genera in 12 countries, using two of these section-specific loci (ASA-10 and ASA-19) along with the RNA polymerase II second largest subunit (rpb2) gene. The majority of strains (57.4%) originated from various cereal crops in Canada, which formed the main focus of our study. Phylogenetic analyses were used to classify strains into section Alternaria species/lineages, demonstrating that the most common species on Canadian cereal crops are A. alternata and A. arborescens. Further population genetic analyses were consistent with A. alternata being a widely distributed species with relatively low levels of geographic isolation (i.e. Canadian isolates did not form distinct clades when compared to other regions). Our expanded sampling of A. arborescens has greatly increased the known diversity of this group, with A. arborescens isolates forming at least three distinct phylogenetic lineages. Proportionally, A. arborescens is more prevalent in Eastern Canada than in Western Canada. Sequence analyses, putative hybrids, and mating-type distributions provided some evidence for recombination events, both within and between species. There was little evidence for associations between hosts and genetic haplotypes of A. alternata or A. arborescens.